الآليات القانونية لحماية الأسرة والمجتمع من التفكك - مطالبي بلقاسم (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
لأجل تحقيق الأمن الأسري ورأب جدران الأسرة الآيلة للتصدع والتفكك ، أورد المشرع الجزائري في قانون الأسرة موادَ تتعلق بهذه الغاية النبيلة ، وعضدها بأخرى في قانون الإجراءات المدنية والإدارية ، بيد أن تحقيق هذه الغاية على الصعيد العملي اعترته جملة من المعوقات منها ما هو راجع إلى النص في حد ذاته ، ومنها ما هو راجع إلى أسباب أخرى ، وقصد الإجابة عن هذه الإشكالية ، وذلك برصد أهم المعوقات لآلية الصلح ، مع اقتراح حلول وآفاق لفاعلية أنجع ، فقد اعتمدت في بناء هذه الورقة على المنهج التحليلي من خلال تحليل النصوص القانونية المتعلقة بالموضوع ؛ لأصل في الختام إلى أن ربط الصلح بقاضي الحكم يعد أهم معوق له ، ما يجعل مأسسته حتمية لا مناص منها . In order to achieve family security and mend the walls of the family that are prone to cracking and disintegration, the Algerian legislator included articles related to this noble goal in the Family Code, supported by another in the Code of Civil and Administrative Procedures, However, achieving this objective on the practical level faced a number of obstacles, some of which are related to the text itself. Including what is due to other reasons, In order to answer this problem, this is by monitoring the most important obstacles to the reconciliation mechanism, with proposing solutions and prospects for more effectiveness .In structuring this study, it relied on the analytical approach by analyzing legal texts and data related to the subject, yet, in the conclusion of the study, that linking reconciliation with the ruling judge is the most important obstacle to it, which makes its institutionalization inevitable and inevitable.